Shaping untuk menurunkan frekuensi gagap psikogenik pada remaja - Mohammad Ikhwanur Rokhim; Zainul Anwar (Procedia : Studi Kasus dan Intervensi Psikologi, 2026)
This case study is based on the assumption that psychogenic stuttering in adolescents emerges as a result of unresolved emotional tension and negative social experiences. The purpose of this study is to identify the psychological dynamics underlying psychogenic stuttering and to evaluate the effectiveness of behavior modification using the shaping technique in reducing stuttering frequency. This study hypothesizes that behavior modification using the shaping technique combined with diaphragmatic breathing relaxation will reduce stuttering frequency and improve verbal communication in adolescents with psychogenic stuttering. The assessment methods included interviews, observation, the WISC, graphic tests (DAP, BAUM, HTP), and the SSCT. Stuttering frequency was measured through observation during communication practice sessions by recording the number of syllable repetitions or difficulties in initiating words in a structured conversation.The intervention was implemented through the shaping technique combined with diaphragmatic breathing relaxation over eight sessions. The results showed a decrease in the frequency of stuttering during a 10-minute conversation, from 11 occurrences to 0 at the follow-up session, accompanied by improvements in self-confidence, social communication skills, and emotional regulation. These findings support that behavior modification using the shaping technique is effective in reducing psychogenic stuttering frequency and enhancing the adolescent’s adaptive functioning.